International recommendations for training future toxicologic pathologists participating in regulatory-type, nonclinical toxicity studies - Bolon, Brad; Barale-Thomas, Erio; Bradley, Alys; Ettlin, Robert A.; Franchi, Carla Adriene da Silva [UNESP]; George, Catherine; Giusti, Anna Maria; Hall, Robert; Jacobsen, Matthew; Konishi, Yoichi; Ledieu, David; Morton, Daniel; et al. (Elsevier Gmbh, Urban & Fischer Verlag, 2011)
The International Federation of Societies of Toxicologic Pathologists (IFSTP) proposes a common global framework for training future toxicologic pathologists who will support regulatory-type - nonclinical toxicology studies. Trainees optimally should undertake a scientific curriculum of at least 5 years at an accredited institution leading to a clinical degree (veterinary medicine or medicine). Trainees should then obtain 4 or more years of intensive pathology practice during a residency and/or on-the-job "apprenticeship," at least 2 years of which must be focused on regulatory-type toxicologic pathology topics. Possession of a recognized pathology qualification (i.e., certification) is highly recommended. A nonclinical pathway (e.g., a graduate degree in medical biology or pathology) may be possible if medically trained pathologists are scarce, but this option is not optimal. Regular, lifelong continuing education (peer review of nonclinical studies, professional meetings, reading, short courses) will be necessary to maintain and enhance one's understanding of current toxicologic pathology knowledge, skills, and tools. This framework should provide a rigorous yet flexible way to reliably train future toxicologic pathologists to generate, interpret, integrate, and communicate data in regulatory-type, nonclinical toxicology studies. (C) 2010 Reprinted by Permission of SAGE Publications Inc. Published by Elsevier GmbH. All rights reserved.
Keywords: Toxicologic pathologists; Education; Training; Experience; Registration; Accreditation; Recognition